Real-Time Ambient Environmental and Noise Pollution Monitoring System in High-Density Areas of Malang City using Internet of Things (IoT) Technology - Yasmin Zafirah; Allin Junikhah; Fuad Dwi Hanggara; Fariz Rifqi Zul Fahmi; Aulia Fikriarini Muchlis (School of Postgraduate Studies, Diponegoro Univer, 2026)
This study evaluated real-time ambient environment and sound pollution monitoring system using Internet of Things (IoT). This system detects wide range of temperature, humidity, fine particulate matter (PM2.5), Carbon monoxide (CO), Carbon dioxide (CO2), and noise level in six traffic areas in Malang City during peak hours. Using a variety of sensors, the system continuously monitors ambient environment and noise pollution at 06:00-07:00, 11:00-12:01, 15:00-16:02. The monitoring tools was placed ±3 meters from the roadside near to the traffic light. Data were collected during peak traffic hours, emphasizing the direct impact of car emissions on air quality. Intense vehicle activity has contributed to increased temperatures and higher particulate matter in specific areas. However, CO, CO₂ and noise levels were observed to remain within acceptable safety thresholds. Notably, this study identified an inverse correlation between temperature and humidity. The IoT-based environmental monitoring system, deployed across six high-traffic locations in Malang, has been successfully implemented and effectively operated. This study investigated environmental factors that greater than threshold using IoT monitoring system deserving further evaluation.